FAKTOR FUNDAMENTAL, SUKU BUNGA DAN NILAI TUKAR TERHADAP RETURN SAHAM - Widyastuti, Tri; Andamari, Basis G. (JURNAL AKUNTANSI DAN AUDITING, 2013)
This research is performed in order to test the influence of the variables Return on Equity (ROE),Debt Equity of Ratio (DER), Earning per Share Log (EPS Log), Interest Rate and Exchange Ratetoward Stock Return of companies that specializes in consumption goods sector that is listed inBEI over period 2008 – 2011. Data analysis with multi linier regression and hypothesis test usedt-test and F-test at level of significance 5%. Besides that, a classic assumption examination whichconsist of data normality test, multicolinierity test, heteroskedasticity test and autocorrelation testis also being done to test the multi linier regression model. Based on normalty test, multicolinieritytest, heteroskedasticity test and autocorrelation test, the multi linier regression model has fulfilthe classic assumption deviation empirical evidence show as EPS Log, and Interest Rate haveinfluence significance toward Stock Return. ROE, DER and Exchange rate do not have influence significance toward Stock Return . Where it was proved that together ROE, DER, EPS Log, Interest Rate and Exchange Rate have influence significance toward Stock Return of the company